(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This article is a historical investigation of some ofGandhi’s endeavors to unite the Hindu and Muslim populaces of India, and alsohis political explores different avenues regarding peaceful resistance. Itgives an diagram of the period starting from his first crusade in South Africato the eve of the Second World War. highlight of Gandhi’s dream to uniteMuslims and Hindus, his resistance to British dominion, and the effects of hispolitical struggles, it introduces parts of the Mahatma’s political moving thatremain to a great extent obscure until this day - a mystery scene still coveredin riddle. His mediation in the Arab-Israeli clash in Palestine hasbeen kept a deliberately protected mystery, decades after Gandhi’s death.Inside the historical and political course of events of Gandhi’s politicalactivities, inside and outside India, this article dissects the conditions thatheaded him to mediate in Palestinian issues, his desires thereof, and theconclusions of his attempts. Magic words: Satytagraha, India. Palestine,Hindu-Muslim unity. Bedouin Israeli clash.